Anion exchange membrane and manufacturing method thereof
Patent Information
- Application Number
- KR1020230191864
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-11-21
- Filing Date
- 2023-12-26
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-12-26
Smart Images

Figure 112023145812774-PAT00040_ABST
Abstract
Description
Technology Field
[0001] The present disclosure relates to an anion exchange membrane and a method for manufacturing the same. Background Technology
[0002] Ion exchange membranes are synthetic resin membranes that selectively allow only one type of ion to pass through, either cations or anions. Cation exchange membranes possess negatively charged functional groups, enabling the selective passage of cations, while anion exchange membranes possess positively charged functional groups, enabling the selective passage of anions. Based on electrodialysis technology, ion exchange membranes are widely used in various fields such as seawater concentration, desalination, purification of organic acids, and recovery of valuable metals. Furthermore, they are being applied to hydrogen production technology via water electrolysis, which has recently garnered attention for securing sustainable energy alongside the issue of CO2 reduction due to global warming. Water electrolysis technologies utilizing ion exchange membranes include cation exchange membrane or proton exchange membrane electrolysis technologies utilizing proton migration, and anion exchange membrane electrolysis technologies utilizing anion exchange membranes in an alkaline solution environment. Anion exchange membrane water electrolysis technology utilizes water electrolysis through the conduction of hydroxide ions. Compared to proton exchange membrane water electrolysis technology that utilizes hydrogen ion conduction, it has the advantage of allowing the use of low-cost water splitting catalysts, so much research is being conducted on it recently.
[0003] These anion exchange membranes can be applied to water treatment systems such as electrodialysis, bipolar membrane electrodialysis, capacitive desalination, and electro-deionization, or to systems such as fuel cells, water electrolysis, reverse electrodialysis, and redox flow cells. Perfluorinated anion exchange membranes can be used as anion exchange membranes, but due to their high cost, hydrocarbon anion exchange membranes are applied in actual systems. However, hydrocarbon anion exchange membranes have limitations in increasing membrane properties such as ion exchange capacity (IEC) because a certain fraction of porous support material exists within the membrane. The problem to be solved
[0004] The present invention provides an anion exchange membrane formed as a self-supporting membrane without a porous polymer support, which has high current density and low hydrogen permeability by increasing the mobility of hydroxide ions, and a method for manufacturing the same. means of solving the problem
[0005] According to one aspect,
[0006] A first polymer having a repeating unit represented by the following chemical formula 1; and
[0007] A second polymer that is a polymer or copolymer of a composition comprising a monomer represented by the following chemical formula 2; comprising
[0008] An anion exchange membrane is provided in which the second polymer is entangled in the network formed by the first polymer to form a semi-interpenetrating polymer network (semi-IPN) structure:
[0009] <Chemical Formula 1>
[0010]
[0011] <Chemical Formula 2>
[0012]
[0013] Among the above chemical formulas 1 and 2,
[0014] R1 to R3 and R 11 to R 14 are independently substituted or unsubstituted C1-C 20 Alkyl groups, substituted or unsubstituted C2-C 20 alkenyl group and -(CH2) n Selected from -N(Q1)(Q2),
[0015] Q1 and Q2 are each hydrogen or a substituted or unsubstituted C1-C3 alkyl group, and
[0016] R 11 and R 12 , R 11 and R 13 , R 11 and R14 , R 12 and R 13 , R 12 and R 14 and R 13 and R 14 Each optionally combines with each other,
[0017] L1 is a single bond and a substituted or unsubstituted C1-C 20 Selected from alkylene groups, and
[0018] a1 is 0 or 1, and if a1 is 0 (L1) a1 is not present and i) R 11 and R 12 and ii) R 13 and R 14 At least one of them is combined with each other, and
[0019] Vi is a vinyl group, and
[0020] X - , Y - and Z - are independent of each other, F - , Cl - , Br - and I - Selected from among,
[0021] p is selected from 60 to 80, and
[0022] q is selected from 20 to 40, and
[0023] The sum of p and q is 100, and
[0024] n, n1, and n2 are each selected from integers greater than or equal to 1.
[0025] According to another aspect,
[0026] A step of mixing the first polymer and the monomer in a solvent;
[0027] Step of casting the mixture onto a substrate;
[0028] A step of forming a film by irradiating a cast mixture with ultraviolet light; and
[0029] A method for manufacturing an anion exchange membrane is provided, comprising the step of peeling off the substrate from the above film. Effects of the invention
[0030] An anion exchange membrane formed as a self-supporting membrane without a porous polymer support and containing both the first polymer and the second polymer described above simultaneously can have a low sheet resistance and a high ion conductivity level, while also having a high ion exchange capacity (IEC). In addition, as the second polymer is formed, it becomes entangled in the network formed by the first polymer to form a semi-interpenetrating polymer network (semi-IPN) structure, and an anion exchange membrane having such a dense structure can have low hydrogen permeability. Specific details for implementing the invention
[0031] Hereinafter, an ion exchange membrane according to one embodiment and a method for manufacturing the same will be described in more detail. The following is presented as an example and is not intended to limit the present invention, and the present invention is defined only by the claims set forth below.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention pertains. In the event of a conflict, the present specification, including definitions, shall prevail.
[0033] Methods and materials similar or equivalent to those described herein may be used in the practice or testing of the present invention, but suitable methods and materials are described herein.
[0034] In this specification, expressions such as "at least one type," "one or more types," or "one or more" preceding the components are capable of supplementing the list of all components and do not mean that they are capable of supplementing the individual components described above.
[0035] In this specification, the term “includes” is used to indicate that other components may be added or / and interposed, rather than excluding other components, unless specifically stated otherwise.
[0036] Unless otherwise specifically defined in this specification, the unit "parts by weight" means the weight ratio between each component.
[0037] The numerical values described in this specification may be understood to include the meaning of "approximately" even if not explicitly stated.
[0038] In this specification, the term "semi-interpenetrating polymer network (semi-IPN) structure" refers to a structure in which only one of two polymer components is selectively crosslinked without affecting the other component.
[0039] In this specification, "carbon numbers a to b" or "C a -C b "a and b of [the expression] refer to the number of carbon atoms of a specific functional group. That is, the functional group may include carbon atoms from a to b. For example, "alkyl group having 1 to 2 carbon atoms" or "C1-C2 alkyl group" refers to an alkyl group having 1 to 2 carbons, namely -CH3 and -CH2CH3.
[0040] In this specification, the term “alkyl” means a branched (broken) or unbranched (straight-chain) aliphatic hydrocarbon. The alkyl group includes, but is not limited to, methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, tert-butyl, pentyl, hexyl, cyclopropyl, cyclopentyl, cyclohexyl, cycloheptyl, etc., and each of these may be optionally substituted or not substituted.
[0041] In this specification, the term "alkylene" means a divalent group having the same structure as "alkyl". The alkylene group includes, but is not necessarily limited to, methylene groups, ethylene groups, propylene groups, butylene groups, pentylene groups, hexylene groups, heptylene groups, etc., and each of these may be optionally substituted or not substituted.
[0042] In this specification, the term "alkenyl" means a monovalent hydrocarbon containing one or more carbon-carbon double bonds at the middle or terminal of an alkyl group. The alkenyl group includes, but is not necessarily limited to, an ethenyl group, a propenyl group, a butenyl group, etc., and each of these may be optionally substituted or not substituted.
[0043] In this specification, a substituent is derived by the exchange of one or more hydrogens from an unsubstituted mother group with another atom or functional group. For example, when a functional group is considered to be "substituted," said functional group is C1-C 40 Alkyl group, C1-C 40 Alkoxy group, C2-C 40 alkenyl group, C2-C 40 alkynyl group, C3-C 40 Cycloalkyl group, C3-C 40 Cycloalkenyl group, C6-C 40 It means that it is substituted with one or more substituents selected from aryl groups, etc. If it is stated that the functional group is "optionally substituted," it means that the said functional group may be substituted with the substituents described above.
[0044] A typical anion exchange membrane includes a porous polymer support acting as a reinforcing material to improve ion conductivity and durability, and has a form in which an electrolyte with anion exchange capability is filled into the porous polymer support. Such anion exchange membranes have problems such as a relatively complex manufacturing process, low hydroxide ion conductivity due to increased sheet resistance, and deterioration of durability and membrane properties due to separation between the cross-linked electrolyte and the reinforcing material during long-term operation.
[0045] The inventors provide an anion exchange membrane having a free-standing film form without including a porous polymer support, thereby solving the aforementioned problems. Accordingly, the anion exchange membrane according to one aspect is clearly different from an anion exchange membrane having an electrolyte with anion exchange capability filled on the surface or inside the pores of a porous polymer support.
[0046] According to one aspect,
[0047] A first polymer having a repeating unit represented by the following chemical formula 1; and
[0048] A second polymer comprising a polymer or copolymer of a composition including a monomer represented by the following chemical formula 2; and
[0049] An anion exchange membrane is provided in which the second polymer is entangled in the network formed by the first polymer to form a semi-interpenetrating polymer network structure:
[0050] <Chemical Formula 1>
[0051]
[0052] <Chemical Formula 2>
[0053]
[0054] Among the above chemical formulas 1 and 2,
[0055] R1 to R3 and R 11 to R 14 are independently substituted or unsubstituted C1-C 20 Alkyl groups, substituted or unsubstituted C2-C 20 alkenyl group and -(CH2) n Selected from -N(Q1)(Q2),
[0056] Q1 and Q2 are each hydrogen or a substituted or unsubstituted C1-C3 alkyl group, and
[0057] R 11 and R 12 , R 11 and R13 , R 11 and R 14 , R 12 and R 13 , R 12 and R 14 and R 13 and R 14 Each optionally combines with each other,
[0058] L1 is a single bond and a substituted or unsubstituted C1-C 20 Selected from alkylene groups, and
[0059] a1 is 0 or 1, and if a1 is 0 (L1) a1 is not present and i) R 11 and R 12 and ii) R 13 and R 14 At least one of them is combined with each other, and
[0060] Vi is a vinyl group, and
[0061] X - , Y - and Z - are independent of each other, F - , Cl - , Br - and I - Selected from among,
[0062] p is selected from 60 to 80, and
[0063] q is selected from 20 to 40, and
[0064] The sum of p and q is 100, and
[0065] n, n1, and n2 are each selected from integers greater than or equal to 1.
[0066] First polymer
[0067] The first polymer may include a quaternary ammonium salt having a repeating unit represented by the above chemical formula 1. The first polymer may serve as the main chain of the anion exchange membrane. The first polymer may form a three-dimensional network. The first polymer may not be chemically bonded to the second polymer. The weight of the first polymer in the anion exchange membrane may be greater than the weight of the second polymer.
[0068] According to one embodiment, at least one of R1 to R3 in Formula 1 is substituted or unsubstituted C1-C 20 It may be an alkyl group. For example, R1 to R3 each are substituted or unsubstituted C1-C 20 It may be an alkyl group. Specifically, each of R1 to R3 may be selected from a methyl group, an ethyl group, and a propyl group.
[0069] In the above chemical formula 1, q can be selected from 20 to 40, for example, q can be selected from 25 to 35. If q is less than 20, physical properties such as sheet resistance, ion conductivity, ion exchange capacity, current density, and hydrogen permeability of the anion exchange membrane may be reduced, and if q is greater than 40, mechanical strength may be reduced, and there may be a problem of reduced solubility when manufactured as a solution.
[0070] Second polymer
[0071] The second polymer may be a crosslinked product of a composition containing a monomer represented by Chemical Formula 2. During the manufacture of the anion exchange membrane, the monomer may be distributed between the three-dimensional networks formed by the first polymer. The monomer may include vinyl groups. Ultraviolet light may be irradiated to form bonds between the monomers via the vinyl groups. The second polymer formed by the polymerization of the monomer may be entangled in the three-dimensional network formed by the first polymer. Accordingly, the anion exchange membrane may have a semi-interpenetrating polymer network structure formed by the first polymer and the second polymer being entangled with each other. That is, the first polymer and the second polymer may be physically entangled rather than chemically bonded. The weight of the second polymer in the anion exchange membrane may be greater than the weight of the first polymer.
[0072] According to one embodiment, the monomer may be represented by any one of the following chemical formulas 2-1 to 2-6:
[0073] <Chemical Formula 2-1>
[0074]
[0075] <Chemical Formula 2-2>
[0076]
[0077] <Chemical Formula 2-3>
[0078]
[0079] <Chemical Formula 2-4>
[0080]
[0081] <Chemical Formula 2-5>
[0082]
[0083] <Chemical Formula 2-6>
[0084]
[0085] Among the above chemical formulas 2-1 to 2-6,
[0086] R11 to R 14 , L1, a1, Vi, Y - , Z - The descriptions for n1 and n2, respectively, are the same as the description of Chemical Formula 2 above. That is, the vinyl group, which is the part polymerized between monomers, can be present at various positions of the benzene group in Chemical Formula 2 above.
[0087] R 11 and N + The bonds of can be single or double bonds, and R 12 and N + The bonds of can be single or double bonds, and R 13 and N + The bonds of can be single or double bonds, and R 14 and N + The bonds of can be single or double bonds. For example, R 11 and R 12 ga combine with each other, and R 13 and R 14 R formed by combining with each other 11 -R 12 -N + -R 14 -R 13 -N + The group can be a pyrazine group.
[0088] For example, R 11 to R 14 If they do not combine, then a1 is 1, so (L1) a1 This can exist. As another example, R 11 and R 12 ga combine with each other and R 13 and R 14 They combine with each other and a1 is 0, so (L1) a1 If this does not exist, a pyrazine group may exist. Another example is R 11 and R 12 ga combine with each other and R 13 and R 14They combine with each other and a1 is 1, so (L1) a1 If this exists, a bicyclo group may exist.
[0089] According to one embodiment, n, n1, and n2 can each be selected from integers from 1 to 10. For example, n, n1, and n2 can each be 1, 2, 3, 4, or 5.
[0090] According to one embodiment, among the above chemical formulas 2 and 2-1 to 2-6, at least one of n1 and n2 may be 1. For example, each of n1 and n2 may be 1.
[0091] According to one embodiment, among the above formulas 2 and 2-1 to 2-6 The group represented by may be represented by any one of the following chemical formulas 3-1 to 3-4:
[0092] <Chemical Formula 3-1>
[0093]
[0094] <Chemical Formula 3-2>
[0095]
[0096] <Chemical Formula 3-3>
[0097]
[0098] <Chemical Formula 3-4>
[0099]
[0100] Each of the above * and *' is a bonding site with an adjacent atom.
[0101] According to one embodiment, the monomer may be one or more selected from the following compounds 1 to 5:
[0102]
[0103]
[0104]
[0105]
[0106] .
[0107] That is, the above monomer N1,N1,N2,N2 -tetramethyl- N1, N2 -bis(4-vinylbenzyl)ethane-1,2-diaminium (compound 1 above; may be referred to as TMVE), N1,N1,N6,N6 -tetramethyl- N1,N6 It may be one or more selected from -bis(4-vinylbenzyl)hexane-1,6-diaminium (compound 2 above; may be referred to as TMVH), 1,4-bis(4-vinylbenzyl)pyrazine-1,4-diium (compound 3 above; may be referred to as VBP), 1,3-bis(4-vinylbenzyl)-1,3,5,7-tetraazaadamantane-1,3-diium (compound 4 above; may be referred to as VTAA), and 1,4-bis(4-vinylbenzyl)-1,4-diazabicyclo[2.2.2]octane-1,4-diium (compound 5 above; may be referred to as VBDAO).
[0108] Among the above chemical formulas 2 and 2-1 to 2-6, "R 11 to R 14 "Those that are not bonded to each other" may refer to the above chemical formula 3-1 or the above compounds 1 and 2.
[0109] Among the above chemical formulas 2 and 2-1 to 2-6, "R 11 and R 12 ga combine with each other, and R 13 and R 14 "Those combined with each other" may refer to the above chemical formulas 3-2 to 3-4 or the above compounds 3 to 5.
[0110] Among the above chemical formulas 2 and 2-1 to 2-6, "a1 is 0, so (L1) a1"This non-existent" may refer to Chemical Formula 3-2 or Compound 2 above. Since a1 is 0, (L1) a1 If this does not exist, i) R 11 and R 12 ☐ combine with each other, and ii) R 13 and R 14 They can combine with each other.
[0111] According to one embodiment, R 11 to R 14 are independently substituted or unsubstituted C1-C5 alkyl groups, substituted or unsubstituted C2-C5 alkenyl groups and -(CH2) n Selected from -N(Q1)(Q2), where Q1 and Q2 are each hydrogen or a substituted or unsubstituted C1-C3 alkyl group, and n can be 0, 1, or 2. For example, R 11 to R 14 The groups can be independently selected from methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, tert-butyl, ethenyl, propenyl, butenyl, -CH2-NHCH3 and -CH2-N(CH3)2.
[0112] According to one embodiment, L1 is a substituted or unsubstituted C1-C 10 It may be an alkylene group. For example, L1 is -CH2-, -(CH2)2-, -(CH2)3-, -(CH2)4-, -(CH2)5-, -(CH2)6-, -(CH2)7-, -(CH2)8-, -(CH2)9- and -(CH2) 10 - Can be selected from
[0113] Vi is It may be a group indicated by , and * is a bonding site with an adjacent atom.
[0114] Y - and Z - They may be identical or different from each other. For example, Y - and Z - Each is Cl - It could be.
[0115] According to one embodiment, the monomer may include two to four nitrogen atoms. For example, the monomer includes two N + It may include. As another example, the monomer comprises two N + and may include 2 Ns.
[0116] According to one embodiment, the composition comprising the monomer represented by Formula 2 may further comprise a photoinitiator. The photoinitiator may be one or more selected from 2-hydroxy-2-methylpropiophenone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, and 1-hydroxy-cyclohexyl-phenyl-ketone.
[0117] anion exchange membrane
[0118] According to one embodiment, the weight of the first polymer included in the anion exchange membrane may be greater than the weight of the second polymer included in the anion exchange membrane. For example, the ratio of the weight of the first polymer to the weight of the second polymer may be 5:0.1 to 5:4. Specifically, the weight of the first polymer included in the anion exchange membrane may be greater than twice the weight of the second polymer included in the anion exchange membrane. The ratio of the weight of the first polymer to the weight of the second polymer may be 5:0.5 to 5:2 or 5:1 to 5:2.
[0119] According to one embodiment, the anion exchange membrane may be a free-standing film. The anion exchange membrane may be a single film. That is, the anion exchange membrane does not include a separate substrate (support). For example, a first polymer or a second polymer is present in any part of the anion exchange membrane.
[0120] According to one embodiment, the anion exchange membrane may not include a porous polymer support. For example, the anion exchange membrane may not include polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylene sulfide, polyetheretherketone, polyethersulfone, polysulfone, polystyrene, polyaryleneethersulfone, and polyetherketone.
[0121] According to one embodiment, the sheet resistance of the anion exchange membrane measured at 25°C and in 1M potassium hydroxide is 0.1Ω·cm 2 up to 1Ω·cm 2 It may be. The above sheet resistance may be calculated according to Evaluation Example 1 to be described later. For example, the sheet resistance of the anion exchange membrane calculated according to Evaluation Example 1 in potassium hydroxide at 25°C and 1M is 0.15 Ω·cm 2 Up to 0.5Ω·cm 2 or 0.2 Ω·cm 2 Up to 0.4Ω·cm 2 It could be.
[0122] According to one embodiment, the ionic conductivity of the anion exchange membrane measured in potassium hydroxide at 25°C and 1 M may be 5 mS / cm to 80 mS / cm. The ionic conductivity may be calculated according to Evaluation Example 2 described below. For example, the ionic conductivity of the anion exchange membrane calculated according to Evaluation Example 2 in potassium hydroxide at 25°C and 1 M may be 5.5 mS / cm to 70 mS / cm, 6 mS / cm to 60 mS / cm, 6.5 mS / cm to 50 mS / cm, 7 mS / cm to 40 mS / cm, 7.5 mS / cm to 35 mS / cm, or 8 mS / cm to 30 mS / cm.
[0123] According to one embodiment, the ion exchange capacity of the anion exchange membrane may be 1.0 meq / g to 3.0 meq / g. The ion exchange capacity may be calculated according to Evaluation Example 3 described below. For example, the ion exchange capacity of the anion exchange membrane may be 1.5 meq / g to 3.0 meq / g, 1.8 meq / g to 3.0 meq / g, 1.5 meq / g to 2.5 meq / g, or 1.8 meq / g to 2.5 meq / g.
[0124] According to one embodiment, the thickness of the anion exchange membrane may be 30 µm to 100 µm. For example, the thickness of the anion exchange membrane may be 40 µm to 80 µm or 50 µm to 70 µm. If the thickness of the anion exchange membrane deviates from the above-described range, physical properties such as durability and mechanical stability, sheet resistance, ion conductivity, ion exchange capacity, and current density of the anion exchange membrane may be degraded.
[0125] Method for manufacturing an anion exchange membrane
[0126] According to another aspect,
[0127] A step of mixing the first polymer and the monomer in a solvent;
[0128] Step of casting the mixture onto a substrate;
[0129] A step of forming a film by irradiating a cast mixture with ultraviolet light; and
[0130] A method for manufacturing an anion exchange membrane is provided, comprising the step of peeling off the substrate from the above film.
[0131] The above solvent may be a co-solvent comprising a first solvent that dissolves the first polymer and a second solvent that dissolves the monomer. An example of the first solvent may be 1-methyl-2-pyrrolidone, and an example of the second solvent may be methanol.
[0132] Examples of the above-mentioned materials include glass plates, polyester films, stainless steel (SUS), etc.
[0133] The method for manufacturing the above anion exchange membrane includes a step of peeling off a substrate, so the manufactured anion exchange membrane does not include a substrate (support). For example, the substrate can be peeled off from the film by immersing the substrate and the film attached to the substrate in water or a potassium hydroxide (KOH) solution, etc.
[0134] According to one embodiment, the ultraviolet light may be selected from ultraviolet A (UVA), ultraviolet B (UVB), ultraviolet C (UVC), and vacuum ultraviolet (VUV). The amount of light from the ultraviolet light is 2,000 mJ / cm². 2 Up to 10,000 mJ / cm 2 It could be.
[0135] According to one embodiment, a method for manufacturing an anion exchange membrane may further include the step of drying the composition or the film at a temperature above room temperature for at least 1 minute to volatilize the solvent. For example, drying may be performed at 50°C to 100°C or 60°C to 80°C for 5 to 60 minutes or 10 to 30 minutes.
[0136] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0137] Example A1
[0138] The first polymer was dissolved in a mixed solvent of 1-methyl-2-pyrrolidone and methanol at 60°C at 25% by weight of the total liquid volume, and then compound 1 was added and stirred at room temperature. At this time, the weight ratio of the first polymer to compound 1 was 5:1. After the first polymer and compound 1 were completely dissolved, 2-hydroxy-2-methylpropiophenone was added as a photoinitiator at 1% by weight of the total liquid volume, and then stirred for about 10 minutes.
[0139] After the melting is complete, the mixture is cast onto a substrate using blade or slot die equipment.
[0140] After casting, 3000 mJ / cm² in the mixture 2 Compound 1 is crosslinked by irradiating it with UVC ultraviolet light of a certain amount. Afterwards, a film is formed by drying it in a hot air oven at 70°C for 20 minutes to volatilize the solvent. An anion exchange membrane with a thickness of 70 μm is prepared by immersing the film attached to the substrate in water or potassium hydroxide (KOH) to peel the substrate from the film.
[0141] Examples A2 to A5
[0142] An anion exchange membrane was prepared in the same manner as in Example A1, except that the compound listed in Table 1 below was used instead of the above compound 1.
[0143] Comparative Example A1 (excluding second polymer)
[0144] The first polymer is dissolved in a mixed solvent of 1-methyl-2-pyrrolidone and methanol at 25% by weight of the total liquid volume at 60°C, and then cooled to room temperature.
[0145] Subsequently, the mixture is cast onto a substrate using a blade or slot die equipment. A film is formed by drying in a hot air oven at 70°C for 20 minutes to volatilize the solvent. An anion exchange membrane with a thickness of 70 μm is prepared by immersing the film attached to the substrate in water or potassium hydroxide (KOH) to peel off the substrate from the film.
[0146] Comparative Examples A2 to A6 (excluding the first polymer)
[0147] As a monomer of the second polymer, the compound listed in Table 1 below is dissolved in a mixed solvent of 1-methyl-2-pyrrolidone and methanol at 25% by weight of the total liquid composition. After the compound is completely dissolved, 2-hydroxy-2-methylpropiophenone is added as a photoinitiator at 1% by weight of the total liquid composition, and then stirred for about 10 minutes.
[0148] After the melting is complete, the mixture is cast onto a substrate using blade or slot die equipment.
[0149] After casting, 3000 mJ / cm² in the mixture 2 Compound 1 is crosslinked by irradiating it with UVC ultraviolet light. Afterwards, it is dried in a hot air oven at 70°C for 20 minutes.
[0150] Comparative Examples B1 to B5 (including a porous polymer support instead of the first polymer)
[0151] A polypropylene (PP) porous polymer support with a thickness of 60 μm (porosity: 51%) was prepared.
[0152] As a monomer of the second polymer, the compound listed in Table 2 below is dissolved in a mixed solvent of 1-methyl-2-pyrrolidone and methanol at 25% by weight of the total liquid composition. After the compound is completely dissolved, 2-hydroxy-2-methylpropiophenone is added as a photoinitiator at 1% by weight of the total liquid composition, and then the composition is prepared by stirring for about 10 minutes.
[0153] The above hydrophilized porous polymer support was immersed in the above composition for 5 minutes to fill the surface of the porous polymer support and the inside of the pores with the above composition.
[0154] A laminate was prepared by pressing a polyester film with a thickness of 50 μm onto the upper and lower surfaces of a porous polymer support filled with the above composition, thereby laminating the polyester film and the porous polymer support.
[0155] 3000 mJ / cm² in the above laminate 2 A second polymer, which is a polymer or copolymer of the compound present on the surface and inside the pores of the porous polymer support, was formed by irradiating with UVC ultraviolet light of a certain amount. An anion exchange membrane was prepared by peeling off the polyester film from the porous polymer support having the second polymer formed on the surface and inside the pores.
[0156] Examples C1-1 to C5-2 and Comparative Examples C1-1 to C5-2 (thickness of anion exchange membrane)
[0157] An anion exchange membrane was prepared in the same manner as Example A1, except that the compound listed in Table 3 below was used as the monomer of the second polymer, and the thickness of the anion exchange membrane was the value listed in Table 3 below.
[0158] Evaluation Example 1 (Sheet Resistance)
[0159] Each anion exchange membrane specimen was cut into a 5cm × 5cm size to prepare samples. The samples were immersed in a 1M KOH solution for at least 12 hours. The measurements were stabilized by placing them between electrodes for measuring sheet resistance under 1M KOH solution conditions.
[0160] The above sample was placed between electrodes for measuring sheet resistance, and the linear resistance (R1) of the anion exchange membrane was measured using an LCR meter (Agilent, E4980A). After removing the anion exchange membrane, the resistance (R2) of the 1M KOH solution was measured. The sheet resistance of the anion exchange membrane was calculated using Equation 1 below.
[0161] <Equation 1>
[0162] Rm = (R1 - R2) × S
[0163] Among the above Equation 1,
[0164] Rm is the sheet resistance (Ω·cm) of the anion exchange membrane 2 ) and,
[0165] R1 is the linear resistance of the anion exchange membrane, and
[0166] R2 is the resistance of the 1M KOH solution, and
[0167] S is the area of the electrode.
[0168] Evaluation Example 2 (Ionic Conductivity)
[0169] The sheet resistance (Rm) of the anion exchange membrane calculated in Evaluation Example 1 above was substituted into Equation 2 below to calculate the ion conductivity.
[0170] <Equation 2>
[0171] Ionic conductivity (mS / cm) = [Thickness of anion exchange membrane (㎛) / Rm (Ω·cm) 2 )] / 10
[0172] Evaluation Example 3 (Ion Exchange Capacity)
[0173] Each anion exchange membrane was cut to a size of 5 cm x 5 cm to prepare samples. The samples were washed with distilled water, and excess moisture was removed with a tissue. 70 mL of 1 M NaCl solution was filled into a vial, and the dried samples were immersed in the 1 M NaCl solution for at least 12 hours for primary pretreatment. Afterward, the samples that had completed the primary pretreatment were washed several times with distilled water, and excess moisture was removed with a tissue. 70 mL of 0.5 M Na2CO3 solution was filled into a vial, and the dried samples were immersed in the 0.5 M Na2CO3 solution for at least 12 hours for secondary pretreatment. Afterward, the samples that had completed the secondary pretreatment were removed from the vial, the remaining solution was titrated with 0.01 M AgNO3 solution, and the volume of AgNO3 solution added during titration was recorded. The above sample was washed several times with distilled water and then dried in a hot air oven at 70°C for more than 1 hour. After drying was completed, the weight of the dried anion exchange membrane was measured. The measured weight of the dried anion exchange membrane was substituted into Equation 3 below to calculate the ion exchange capacity (IEC).
[0174] <Equation 3>
[0175] IEC(meq / g) = [Volume of titrant (mL) x 0.01] / Weight of dried anion exchange membrane (g)
[0176] Evaluation Example 4 (Current Density)
[0177] Each anion exchange membrane specimen was cut into a 5cm × 5cm size to prepare samples. After pre-treating the samples by immersing them in a 1M KOH solution at room temperature for 12 hours, the current density was measured by applying a constant voltage from 1.5V to 2V using a water electrolysis system and recording the current value.
[0178] Evaluation Example 5 (Appearance Evaluation)
[0179] Each anion exchange membrane was evaluated by visually inspecting its appearance using the following criteria.
[0180] · Good: The surface is smooth, and no cracks or peeling occur.
[0181] · Defect: Surface is not smooth, or cracks or peeling occur
[0182] Evaluation Example 6 (Leak Evaluation)
[0183] Each anion exchange membrane specimen was cut into a 5cm × 5cm size to prepare samples. After connecting the samples to a unit cell, hydrogen at a pressure of 20kPa was injected into the cathode (at this time, the anode port was open and at atmospheric pressure). Waited for at least 5 minutes to allow the internal pressure of the unit cell to stabilize. After 1 minute from the point where hydrogen was injected, the hydrogen pressure was measured using a manometer on the side opposite the anion exchange membrane.
[0184] No. High molecular weight monomer of the second polymer Thickness of the anion exchange membrane (㎛) Sheet resistance (Ω·cm) 2 ) Ionic conductivity (mS / cm) Ion exchange capacity (meq / g) Current density (mA at 1.8V) Appearance evaluation Leakage rating (Barrer at 10 bar) Example A1 Chemical formula 1 Compound 1 70 0.25 28 2.1 1000 Good 5 Example A2 Chemical formula 1 Compound 2 70 0.27 26 2.0 1000 Good 6 Example A3 Chemical formula 1 Compound 3 70 0.37 19 2.0 800 Good 4 Example A4 Chemical formula 1 Compound 4 70 0.42 17 2.0 950 Good 4 Example A5 Chemical formula 1 Compound 5 70 0.25 28 2.2 1000 Good 4 Comparative Example A1 Chemical formula 1 - 70 0.18 39 1.5 600 Good 30 Comparative Example A2 - Compound 1 Unable to unveil Comparative Example A3 - Compound 2 Comparative Example A4 - Compound 3 Comparative Example A5 - Compound 4 Comparative Example A6 - Compound 5
[0185] From Table 1 above, in the case of Comparative Examples A2 to A6, in which the first polymer having a repeating unit represented by Chemical Formula 1 was not used, membrane formation was impossible. This indicates that when using the second polymer utilizing the monomer represented by Chemical Formula 2 without the first polymer, a separate configuration is required to be applied as an anion exchange membrane. Accordingly, Comparative Examples B1 to B5, to which a separate configuration is applied, will be described later with reference to Table 2 below.
[0186] The anion exchange membranes prepared according to Examples A1 to A5 have a resistance of 0.05 Ω·cm2 It has a low sheet resistance of the level below and a high ion conductivity of 15 mS / cm or higher, and has a higher ion exchange capacity than the anion exchange membrane according to Comparative Example A1 using the first polymer without the second polymer, and it can be seen that it has low hydrogen permeability as the hydrogen pressure is low according to the leak evaluation.
[0187] No. porous support material monomer of the second polymer Thickness of the anion exchange membrane (㎛) Sheet resistance (Ω·cm) 2 ) Ionic conductivity (mS / cm) Ion exchange capacity (meq / g) Current density (mA at 1.8V) Appearance evaluation Leakage rating (Barrer at 10 bar) Comparative Example B1 PP Compound 1 70 1.7 4.1 1.0 137 Good 0 Comparative Example B2 PP Compound 2 70 1.2 5.8 1.0 208 Good 0 Comparative Example B3 PP Compound 3 70 1.8 3.9 1.1 127 Good 0 Comparative Example B4 PP Compound 4 70 1.3 5.4 1.7 265 Good 0 Comparative Example B5 PP Compound 5 70 1.2 5.8 1.6 280 Good 0
[0188] In the case where a second polymer using a monomer represented by Chemical Formula 2 is used without the first polymer, a self-supporting anion exchange membrane cannot be manufactured, so an anion exchange membrane in which the second polymer exists on the surface of a porous polymer support and inside the pores can be manufactured to compare physical properties.
[0189] Referring to Tables 1 and 2 above, it can be seen that the anion exchange membrane prepared according to Examples A1 to A5, which includes the first polymer and the second polymer without a porous polymer support, has lower sheet resistance, higher ion conductivity, higher ion exchange capacity, and higher current density than the anion exchange membrane prepared according to Comparative Examples B1 to B5, which uses a porous polymer support instead of the first polymer.
[0190] No. First polymer monomer of the second polymer Thickness of the anion exchange membrane (㎛) Sheet resistance (Ω·cm) 2 ) Ionic conductivity (mS / cm) Ion exchange capacity (meq / g) Current density (mA at 1.8V) Appearance evaluation Leakage rating (Barrer at 10 bar) Example C1-1 Chemical formula 1 Compound 1 30 0.2 15 1.9 1050 Good 17 Example C1-2 Chemical formula 1 Compound 1 100 0.3 33 2.2 920 Good 4.8 Comparative Example C1-1 Chemical formula 1 Compound 1 20 Unable to measure due to weak durability error Unable to measure due to weak durability Comparative Example C1-2 Chemical formula 1 Compound 1 110 0.42 26 2.2 780 Good 4 Example C2-1 Chemical formula 1 Compound 2 30 0.25 12 1.9 1020 Good 18 Example C2-2 Chemical formula 1 Compound 2 100 0.3 33 2.1 905 Good 5.8 Comparative Example C2-1 Chemical formula 1 Compound 2 20 Unable to measure due to weak durability error Unable to measure due to weak durability Comparative Example C2-2 Chemical formula 1 Compound 2 110 0.31 35 2.2 729 Good 4.2 Example C3-1 Chemical formula 1 Compound 3 30 0.35 8.6 1.8 810 Good 12 Example C3-2 Chemical formula 1 Compound 3 100 0.41 24 2.1 708 Good 3.8 Comparative Example C3-1 Chemical formula 1 Compound 3 20 0.33 6 1.8 800 Good 15 Comparative Example C3-2 Chemical formula 1 Compound 3 110 0.48 23 2.1 625 Good 3.8 Example C4-1 Chemical formula 1 Compound 4 30 0.38 7.9 1.8 970 Good 19 Example C4-2 Chemical formula 1 Compound 4 100 0.50 20 2.0 803 Good 4 Comparative Example C4-1 Chemical formula 1 Compound 4 20 0.37 5.4 1.7 992 Good 22 Comparative Example C4-2 Chemical formula 1 Compound 4 110 0.58 19 2.1 725 Good 3.7 Example C5-1 Chemical formula 1 Compound 5 30 0.23 13 2.0 1020 Good 17 Example C5-2 Chemical formula 1 Compound 5 100 0.27 37 2.3 952 Good 3.9 Comparative Example C5-1 Chemical formula 1 Compound 5 20 0.20 10 1.9 1005 Good 24 Comparative Example C5-2 Chemical formula 1 Compound 5 110 0.30 37 2.3 874 Good 3.8
[0191] Referring to Tables 1 and 3 together, it can be seen that the anion exchange membranes prepared by Examples A1 to A5 and C1-1 to C5-2, with a thickness of 30 μm to 100 μm, have stronger durability or lower sheet resistance, higher current density, higher ion exchange capacity, and / or lower hydrogen permeability than the anion exchange membranes prepared by Comparative Examples C1-1 to C5-2, with a thickness outside the range of 30 μm to 100 μm.
[0192] From the above-described evaluation examples 1 to 6, it can be seen that the anion exchange membranes prepared by Examples A1 to A5 and C1-1 to C5-2 are suitable for use in electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization, or water electrolysis systems.
[0193] The foregoing description is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical spirit or essential features of the invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.
Claims
Claim 1 An anion exchange membrane comprising: a first polymer having repeating units represented by the following chemical formula 1; and a second polymer being a polymer or copolymer of a composition including a monomer represented by the following chemical formula 2; wherein the second polymer is entangled in the network formed by the first polymer to form a semi-interpenetrating polymer network (semi-IPN) structure, and the anion exchange membrane not comprising a porous polymer support: <Chemical Formula 1> <Chemical Formula 2> In the above chemical formulas 1 and 2, R1 to R3 and R 11 to R 14 are independently substituted or unsubstituted C1-C 20 Alkyl groups, substituted or unsubstituted C2-C 20 alkenyl group and -(CH2) n Selected from -N(Q1)(Q2), where Q1 and Q2 are each hydrogen or a substituted or unsubstituted C1-C3 alkyl group, and R 11 and R 12 , R 11 and R 13 , R 11 and R 14 , R 12 and R 13 , R 12 and R 14 and R 13 and R 14 Each optionally combines with each other, and L1 is a single bond and a substituted or unsubstituted C1-C 20 Selected from alkylene groups, a1 is 0 or 1, and when a1 is 0, i) R 11 and R 12 and ii) R 13 and R 14 At least one of them is combined with each other (L1) a1 does not exist, Vi is a vinyl group, and X - , Y - and Z - are independent of each other, F - , Cl - , Br - and I - Selected from among, p is selected from 60 to 80, q is selected from 20 to 40, the sum of p and q is 100, and n1 and n2 are each selected from integers greater than or equal to 1. Claim 2 In paragraph 1, R1 to R3 each have a substituted or unsubstituted C1-C 20 Alkyl group, anion exchange membrane. Claim 3 In claim 1, the monomer is an anion exchange membrane represented by any one of the following chemical formulas 2-1 to 2-6: <Chemical Formula 2-1> <Chemical Formula 2-2> <Chemical Formula 2-3> <Chemical Formula 2-4> <Chemical Formula 2-5> <Chemical Formula 2-6> . Claim 4 An anion exchange membrane according to claim 1, wherein at least one of n1 and n2 is 1. Claim 5 In claim 1, among the above chemical formula 2 Anion exchange membrane represented by any one of the following chemical formulas 3-1 to 3-4, with the group indicated by: <Chemical Formula 3-1> <Chemical Formula 3-2> <Chemical Formula 3-3> <Chemical Formula 3-4> Each of the above * and *' is a bonding site with an adjacent atom. Claim 6 Anion exchange membrane according to claim 1, wherein the monomer is one or more selected from the following compounds 1 to 5: . Claim 7 An anion exchange membrane according to claim 1, wherein the weight ratio of the first polymer to the second polymer is 5:0.1 to 5:
4. Claim 8 Anion exchange membrane according to claim 1, wherein the composition further comprises a photoinitiator, and the photoinitiator is one or more selected from 2-hydroxy-2-methylpropiophenone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone and 1-hydroxy-cyclohexyl-phenyl-ketone. Claim 9 In claim 1, the anion exchange membrane is a free-standing film. Claim 10 delete Claim 11 In claim 1, the sheet resistance is 0.1 Ω·cm in potassium hydroxide at 25°C and 1 M. 2 up to 1Ω·cm 2 Phosphorus, anion exchange membrane. Claim 12 An anion exchange membrane according to claim 1, having an ionic conductivity of 5 mS / cm to 80 mS / cm in potassium hydroxide at 25°C and 1 M. Claim 13 An anion exchange membrane according to claim 1, having an ion exchange capacity of 1.0 meq / g to 3.0 meq / g. Claim 14 An anion exchange membrane having a thickness of 30㎛ to 100㎛ in claim 1. Claim 15 A method for manufacturing an anion exchange membrane not comprising a porous polymer support, comprising the steps of: mixing the first polymer of claim 1 and the monomer of claim 1 in a solvent; casting the mixture onto a substrate; irradiating the cast mixture with ultraviolet light to form a film; and peeling off the substrate from the film. Claim 16 A method for manufacturing an anion exchange membrane according to claim 15, wherein the ultraviolet light is selected from ultraviolet A (UVA), ultraviolet B (UVB), ultraviolet C (UVC) and vacuum ultraviolet (VUV).
Citation Information
Patent Citations
membrane
JP2023547043A
Composite membrane based on polyphenylene oxide, preparation method thereof and anion-exchange membrane for fuel cell comprising the same
KR1020190024312A
Anion-exchange membrane, preparation method thereof and alkaline anion-exchange membrane fuel cell comprising the same
KR1020200126562A
Anion exchange membrane
KR1020230151778A